Umbilical Vein Pulse Wave Spectral Analysis: A Possible Method for Placental Assessment Through Evaluation of Maternal and Fetal Flow Components. (21st December 2021) - Rubin, Jonathan M.; Fowlkes, J. Brian; Pinter, Stephen Z.; Treadwell, Marjorie C.; Kripfgans, Oliver D.
Abstract : Objectives: Placental blood flow analysis is complicated by having both maternal and fetal flow components. Using the Fast Fourier Transform (FFT) of the umbilical venous pulse wave spectra (PW) envelope, we could simultaneously assess maternal/fetal blood flow in the placenta and investigate if normal and intrauterine growth restriction (IUGR)/pre‐eclamptic pregnancies could be distinguished. Methods: This retrospective study included normal gestations (N = 11) and gestations with IUGR, pre‐eclampsia, or both (N = 13). Umbilical vein PW were acquired and spectral envelopes were identified as a function of time and analyzed by FFT. Base‐10 logarithms of the ratios of the maternal/fetal spectral peaks (LRSP) were compared in normal and IUGR/pre‐eclamptic populations (two‐tailed t ‐test). Body mass index (BMI), gestational age at scan time, placental position, and weight‐normalized umbilical vein blood volume flow (two‐tailed t ‐test, analysis of variance [ANOVA] analysis) were tested. P  < .05 was considered significant. Results: The LRSP for normal and IUGR/pre‐eclamptic pregnancies were 0.141 ± 0.180 and −0.072 ± 0.262 (mean ± standard deviation), respectively ( P  = .033). We detected differences between normal gestations and combinations of LRSP and weight‐normalized umbilical venous blood flows. Placental effects based on LRSPs and blood flow may act synergistically in cases with both pre‐eclampsia and IUGR ( P  = .014). No other significant associations were seen. Conclusions: In this preliminary study, we showed that umbilical venous flow contains markers related to placental maternal/fetal blood flow, which can be used to assess IUGR and pre‐eclampsia. When coupled with umbilical cord blood flow, this new marker may potentially identify the primary causes of the two conditions.